Metode Context, Input, Process, Dan Product Dalam Evaluasi Program Kerja Bumdes Desa Sunda Kelapa - Nursanty Nursanty; Achmad Aminudin; Kahar Hakim (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2022)
Poverty is a problem that currently still needs solutions to overcome the problem. One of the community welfare improvement programs is the establishment of Village-Owned Enterprises (BUMDes). The policy to form BUMDes in each village aims to create an independent village that has the welfare and good economy of its people. BUMDes are not just formed and then run the program. However, another thing that is also important to do is to evaluate the management of BUMDes itself. The purpose of this activity is to socialize and provide assistance in the evaluation method of a good BUMDes work program so that it can find shortcomings of management and opportunities that can be used to improve the results of the BUMDes work program. In this activity BUMDes which became the focus of assistance is BUMDes in Sunda Kelapa Village, Central Bengkulu Regency. Providing knowledge about the CIPP method as a method to evaluate bumdes work programs. Assistance was carried out because from the results of the activity it was found that the evaluation of the BUMDes work program of Sunda Kelapa Village had not been maximized so that the problem of shortcomings and opportunities from BUMDes itself had not been achieved to the maximum. Pnedampinga needs to be done by related parties so that BUMDes Sunda Kelapa Village can be managed properly so that it can improve the welfare of its people.